Components Design of Cube Cutter for Fruit and Meat: Strength Analyses Under Static and Fatigue Conditions - Antonio, Ryan; Sutrisno, Dwiartha Pambudi Alif; Triawan, Farid (Department of Mechanical and Industrial Engineering, 2023)
Food preparation is one of the longest and the most time consuming part in cooking a food. In the preparation phase, the food ingredients are often needed to be cut into cube shape or stick shape. Besides that, most of the small food industry needs to serve a lot of customers while having limited number of workers, causing the workers to be tired even before the cooking process begin. For this reason, this paper proposes a design idea of a cutting tool that can cut food ingredients into cube and stick shape. This design is also completed with the strength analysis to evaluate the components’ safety for applied force of 50 N. Furthermore, the strength analysis was done by a theoretical approach of static and fatigue loading. According to the analysis, the cutting tool has a safety of more than 3.7 for static loading and 2.14 for fatigue loading. This paper is expected to be used as a reference to create a cutting tool that can help workers in Indonesia.